Draft Annual Plan 1986-87 Government of Himachal Pradesh - Planning Commission (Planning Commission, 1986)
Himachal Pradesh came into being by merger of thirty and odd princely hill States on 15th April, 1944 & underwent a series of metamorphic changes, both political and administrative, till it became the eighteenth State of Indian Union on 25th January, 1971. Subsequently, reorganisation of districts in 1972 gave Himachal Pradesh the shape as it exists today. Himachal Pradesh has an area of 55,673 sq. kms and a population of 81 lakh according to 1981 census. The density of population is 77 persons per square kilometre as compared to 216 at the all lndia level. As much as 92 per cent of the population lives in rural areas and the remaining, 8 per cent is located in 46 towns. Scheduled Castes form 24.6 per cent of the population while Scheduled Tribes account for 4.6 per cent. The areas comprising of Kinnaur district, Lahaul and Spiti district and Pangi and Bharmour tehsils of Chambi district form the tribal areas of the Pradesh.
Planning Department Government of Himachal Pradesh